2020
DOI: 10.1177/0145561320905731
|View full text |Cite
|
Sign up to set email alerts
|

Sphenoid Wing Meningioma Presenting as Sudden Sensorineural Hearing Loss: A Case Report and Literature Review

Abstract: Sphenoid wing meningiomas are tumors that typically present with vision deterioration and neurological changes due to their proximity to the sella, cavernous sinus, and other vital structures. Some unusual symptoms have also been described in the literature, such as cognitive dysfunction, parkinsonism, and intracerebral hemorrhage. In this report, we detail another unusual case of sphenoid wing meningioma in a 63-year-old female who presented with left sudden sensorineural hearing loss. A brief review of the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Meningiomas are intracranial tumors arising from arachnoid cap cells and are the most common (30%) non-glial central nervous system (CNS) neoplasm in adults among other primary brain tumors [ 8 ]. Sphenoid wing meningioma accounts for about 20% of meningiomas cases, with its classic symptoms are proptosis, ophthalmoparesis, and progressive visual acuity impairment, in addition to the general symptoms of meningiomas similar to other extra-axial intracranial tumor manifestations due to compression of CNS [ 9 ]. As in our case, extensive hyperostosis is pathognomonic of sphenoid wing meningioma in radiology imaging; a homogeneous hyperdense mass will be seen on CT-scan, which is evenly enhanced by contrast administration.…”
Section: Discussionmentioning
confidence: 99%
“…Meningiomas are intracranial tumors arising from arachnoid cap cells and are the most common (30%) non-glial central nervous system (CNS) neoplasm in adults among other primary brain tumors [ 8 ]. Sphenoid wing meningioma accounts for about 20% of meningiomas cases, with its classic symptoms are proptosis, ophthalmoparesis, and progressive visual acuity impairment, in addition to the general symptoms of meningiomas similar to other extra-axial intracranial tumor manifestations due to compression of CNS [ 9 ]. As in our case, extensive hyperostosis is pathognomonic of sphenoid wing meningioma in radiology imaging; a homogeneous hyperdense mass will be seen on CT-scan, which is evenly enhanced by contrast administration.…”
Section: Discussionmentioning
confidence: 99%
“…Tumors, including meningioma, in the cerebellopontine area are a common cause of sudden deafness. Toro et al 14 reported a case of sphenoid wing meningioma with sudden deafness as the primary symptom. Due to the long duration of sudden deafness and the failure to perform related imaging tests at the time of onset, we cannot establish a correlation between the occurrence of initial sudden deafness and the existence of meningioma of the middle ear.…”
Section: Discussionmentioning
confidence: 99%
“…By the year 2050, it is expected that more than 2.5 billion people will have some degree of hearing loss, and 700 million will have severe hearing loss [1]. The causative factors contributing to hearing loss include, among others, occupational [2] or during-leisure [3] noise exposure, the use of ototoxic medications [4][5][6], mutations in genes essential for auditory function [7], compression of auditory tissues by tumors (vestibular schwannomas or meningiomas) [8,9], or the effects of cardiovascular diseases [10]. However, one of the most common causes of hearing loss is the aging process [11,12].…”
Section: Introductionmentioning
confidence: 99%